APAKAH MANAJEMEN LABA MERUPAKAN VARIABEL INTERVENING (UNIT ANALISIS PERUSAHAAN PERTAMBANGAN BEI PERIODE 2012-2015) - Irene Sukma Lestari Barus; Tetty Lasniroha Sarumpaet; renny maisyarah; Edrida Pulungan (Universitas Negeri Medan (UNIMED), 2018)
This research is motivated by coal price weakened slightly in the last 3 months. Based on data from the Ministry of Energy and Mineral Resources, the price of coal in March 2017 declined as well as the coordinator of the alleged manipulation of sales reports occurred PT Kaltim Prima Coal (KPC), PT Arutmin Indonesia (Arutmin), and the two companies, PT Bumi Resources Tbk Earth) between 2003-2008, while according to the Futures Trading Supervisory Agency, coal prices continue to tend to decline since November 2011 until now. Coal prices in the first three months, lower than the price in the same period last year while coal production in the period January - March 2012 actually increased high. The research data is panel data obtained from Indonesia Stock Exchange Period 2012 – 2015 which using purposive sampling and analyzed by path analysisand Eviews 9.0 program. The study aims to know that earnings management is an intervening variable that connects the leverage with the quality of profit. The result of analysis shows that earnings management is intervening variable to earnings quality but to leverage is not an intervening at Mining Company registered in BEI period 2012-2015.